Gravitational Wave and Quantum Graviton Interferometer Arm Detection of Gravitons - John W. Moffat (Universe)
This paper explores the quantum and classical descriptions of gravitational wave detection in interferometers like LIGO. We demonstrate that a graviton scattering and quantum optics model succeeds in explaining the observed arm displacements, while the classical gravitational wave approach and a quantum graviton energy method also successfully predict the correct results. We provide a detailed analysis of why the quantum graviton energy approach succeeds, highlighting the importance of collective behavior and the quantum–classical correspondence in gravitational wave physics. Our findings contribute to the ongoing discussion about the quantum nature of gravity and its observable effects in macroscopic physics.